Patient compliance and mandible fractures: a prospective study. Issue 6 (June 2019) - Hurrell, M.J.L.; David, M.C.; Batstone, M.D.
Abstract: Fractures of the facial skeleton place a burden on healthcare systems at the individual and population level. It is suggested that a high proportion of such patients are non-compliant with various aspects of their care. It stands to reason that non-compliance would contribute to adverse outcomes and increased costs in general. The intent of this study was two-fold: to determine factors associated with poor compliance in the studied population of 215 patients with 359 mandible fractures, and to determine whether poor compliance is associated with an increased incidence of treatment complications. Being male, an illicit drug user, non-employed, and living furthest from care were the factors associated with non-compliance in the studied population. Compliance with soft diet, mouthwash, oral antibiotics, cigarette cessation, and review appointment attendance was 74%, 96%, 96%, 16%, and 58%, respectively. Global compliance scores of low, medium, and high were assigned to 27%, 59%, and 14% of participants, respectively. None of the individual postoperative compliance variables was found to be significantly associated with outcomes of treatment at the 5% level. Borderline associations were found. Globally non-compliant patients were significantly more likely to experience wound dehiscence. The utility of the current postoperative regimen should be further elicited.